Polysaccharides from Trichosanthes Fructus via Ultrasound-Assisted Enzymatic Extraction Using Response Surface Methodology. (25th September 2017) - Chen, Fujia; Li, Dahong; Shen, Hongqi; Wang, Chunhong; Li, Enzhong; Xing, Huihui; Guo, Li; Zhao, Qingchun; Shi, Junhao; Nguyen, Hoang; Liu, Jiayang
Abstract : An efficient procedure for ultrasound-assisted enzymatic extraction of crude polysaccharides from Trichosanthes Fructus (crude TFP) using response surface methodology (RSM) was developed. The Box–Behnken design was applied to optimize the effects of pH (X 1 ), enzyme amount (X 2 ), extraction temperature (X 3 ), and liquid-to-solid ratio (X 4 ) on the extraction. The statistical analysis indicated that the independent variables (X 4, X 2, and X 3 ), the quadratic coefficients (X 1 2, X 2 2, X 3 2, and X 4 2 ), and the interaction coefficient (X 1 X 3 ) had significant impact on the yield of crude TFP. The optimal conditions were determined as follows: pH 4.5, enzyme amount 5000 u/g, extraction temperature 45°C, and liquid-to-solid ratio 30 ml/g. The experimental yield of crude TFP was 6.58%, which was very close to the predicted yield of 6.71%. TFPI was then purified and characterized with Sephadex G-100 column, UV-Vis, GPC, and FT-IR. The average molecular weight of TFPI was calculated to be 1.49 × 10 5 Da. TFPI exhibited strong reducing power and possessed not only remarkable scavenging activities against ABTS + and DPPH radicals, but also high antitumor activities in C4-2, DU145, and PC3 cells. The results suggest that Trichosanthes Fructus and TFPI could be a novel potent natural medicine with antioxidant and antitumor activities.